Między Kommune 1 a „niedzielną pieczenią”. Krautrock w świetle koncepcji komunizmu kwasowego - Idzikowski, Kamil (Praktyka Teoretyczna, 2021)
The article examines selected phenomena of the so-called krautrock, i.e. West German rock music of the late 1960s and the 1970s. The analysis is based on Mark Fisher's concept of acid communism and the related issue of collective subjectivity. The author distinguishes two opposing tendencies in the music discussed, the first one being the fascination with the collective that goes back to the student protests of 1967–1968, and the second one being the (re)appreciation of individual perspective, which manifested itself e.g. in an increased interest in spirituality and a certain kind of social criticism performed from a distanced position. Focusing on the relationship between the individual and the group, the article analyzes a number of songs and albums that have received little or no attention from researchers up to now.